ROC analysis data and predictors of rehabilitation effectiveness in patients with type 2 diabetes mellitus - T.H. Bakaliuk; N.R. Makarchuk; H.O. Stelmakh; V.I. Pankiv; L.B. Pavlovych; O.D. Bilous; I.I. Kamyshna (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Type 2 diabetes mellitus (T2DM) is a serious chronic disease that significantly impacts quality of life and is one of the leading causes of disability worldwide. Effective rehabilitation for such patients contributes to the improvement of their functional status, reduces the risk of complications, and enhances the overall prognosis. Identifying predictors of the effectiveness of rehabilitation measures allows for the individualization of treatment approaches and optimization of therapeutic strategies. Using ROC analysis to evaluate the diagnostic accuracy of these predictors ensures the reliability of the obtained results and enables more accurate prediction of rehabilitation outcomes. The aim of the study is to identify predictors of the effectiveness of rehabilitation measures in patients with T2DM and to evaluate their diagnostic accuracy using ROC analysis. This will enable the optimization of rehabilitation programs, increase their effectiveness, and improve the quality of life for patients. Materials and methods. To predict the effectiveness of rehabilitation in diabetic polyneuropathy, 95 patients with T2DM were examined. Descriptive statistics, correlation analysis, and ROC analysis were used to evaluate the diagnostic accuracy of predictors of rehabilitation effectiveness. Results. The analysis indicates a significant association between tobacco smoking status and the effectiveness of rehabilitation. Current smokers have the lowest rehabilitation effectiveness scores, followed by those who quit smoking, with non-smokers having the highest scores. The findings indicate that employment status significantly affects the effectiveness of rehabilitation. The results suggest that higher glycated hemoglobin (HbA1c) levels are moderately associated with decreased rehabilitation effectiveness scores. Patients with higher HbA1c levels, particularly those in the 14–20 range, show significantly worse rehabilitation outcomes compared to those with lower HbA1c levels. The higher DN4 scores are moderately associated with decreased rehabilitation effectiveness scores. Conclusions. There is a significant association between smoking status and rehabilitation effectiveness. Non-smokers have the highest rehabilitation effectiveness scores. Socioeconomic factors, such as employment, should be considered when designing rehabilitation programs. Higher HbA1c levels are moderately associated with decreased rehabilitation effectiveness scores. Neuropathic pain severity, as measured by DN4, influences rehabilitation outcomes.